"São Paulo Faz Escola": muda a abordagem de progressões na sala de aula? - Carvalho, Marcelly Mingorancia de (2010)
This study reports a research aimed study which objective was investigate the changes that have occurred in relation to the work of teachers in the High School of the State chain of São Paulo, face to the material sent by the Education Department of the Sao Paulo State in 2008.This material provides a prior work with pattern generalization activities of several sequences before presenting progressions themselves The relevance of this research justify itself by the importance of the topic: "Observation of regularities and generalization of patterns," pointed out by researchers such as Vale and Pimentel (2005), Vale et al (2005) and Lee (1996), as a device that is not only attract and motivate students during the course of these activities but also promote the development and manifestation of students' algebraic thinking. To collect the data I have elaborated and performed semi-structured interviews with five teachers from state schools, based on the ideas of the Didactic Engineering, as Machado (2008).The interview analysis showed that it was unanimous the acceptance and approval of teachers concerning to this material, as well as provided significant changes in the teachers classes, and have been influenced teachers who ignored the issue at hand